EFFECTIVENESS OF THE HEALTH BELIEF MODEL PROGRAM ON COVID-19 PREVENTION BEHAVIOR AMONG SHAN FEMALE MIGRANT WORKERS CHIANGMAI - Khampan, Yingcharm; Moolphate , Saiyud; Jaitae, Samart (Journal of MCU Nakhondhat, 2024)
This research article aims to Study the effectiveness of the health belief promotion program on COVID-19 disease prevention behavior. Among Shan female migrant workers This was quasi-experimental research with two groups measuring before and after. Compare the mean differences in health beliefs. and average behavior for preventing COVID-19 disease Between the experimental group and the control group and compared in the experimental group Before and after receiving the program sample group It was an experimental group of 45 people and a control group of 45 people of Shan female migrant workers. The experimental group will receive a program to promote health beliefs towards COVID-19 prevention behaviors for a period of 6 weeks. Research statistics and data analysis. Compare the means before and after the trial using Paired t-test. Compare the means between groups using independent t-test. The results found that the effectiveness of the health belief promotion program on COVID-19 disease prevention behavior. When comparing the experimental group and the control group after receiving the program. The experimental group had a mean behavior score of 2.78, the control group had a mean behavior score of 1.52, which increased on average by 1.53, and the mean value of health beliefs increased by 0.54, which was statistically significant at the 0.05 level and the results were compared in the experimental group. Before and after receiving the program, the experimental group had a mean behavior score after receiving the program of 3.32, higher than before receiving the program. The mean behavior score was 2.78, which increased on average by 0.57, and the mean value of health beliefs increased by 2.11, with statistical significance at the 0.05 level. It is seen that the program promotes health beliefs towards COVID-19 disease prevention behaviors. Effective in changing behavior to prevent COVID-19 disease.